Nonlinear analysis for performance characterization of a photoparametric amplifier - Idrus Sutan Nameh, Sevia Mahdaliza; Green, Roger J.; Mohd. Supa'at, Abu Sahmah (2005)
The photoparametric amplifier (PPA) combines optical detection and amplification within a single device. The amplifier operation is based on the non-linear characteristics of the photodiode and therefore, the mechanism constituting gain is highly non-linear and different to that in a conventional amplifier/mixer chain. The PPA has been successfully simulated using a nonlinear microwave simulator to perform harmonics balance analysis, which represented actual photodiode model and nonlinear dynamic capacitance behaviour. The simulation predicted a PPA up-conversion gain as high as 43 dB and this agreed with conventional theoretical analysis. The up-converter gain has been shown to be directly related to the level of pump input and signal input. If there is a limit to pump power, then the gain may be recovered by appropriate adjustment of the ratio of pump to signal frequencies. In this article, the theory of operation, the device structure of the PPA and its characteristic is presented.